PATHOGENIC BEHAVIOUR OF ALTERNARIA ALTERNATA AND PHYTOTOXICITY OF ITS CULTURE FILTRATES ON LEPIDIUM SATIVUM: A MEDICINAL HERB OF IMMENSE PHARMACOLOGICAL POTENTIAL - PUSHPANJALI WAGH, SANDEEP SINHA, HARVINDER KUMAR SINGH ,U. K. KHARE, (The Bioscan, 2013)
Alternaria alternata causing leaf spot in Lepidium sativum was isolated and purified from diseased leaf tissues collected from collected from the Medicinal and Aromatic plant garden, Department of Crop and Herbal Physiology, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (M.P.); isolated and purified on Potato Dextrose Agar media. Microscopic examination of a seven days old culture revealed hyaline, septate and branched mycelia, conidiophores with 30.0-80.2 µ length and 3-6 µ width and obclavate to obpyriform conidia (23-30 x 9.2-12.7 µ) with short conical beak arranged in acropetal fashion. The isolated culture and its culture filtrates were inoculated to germinated seedlings of chandrasur and also incubated with healthy leaves in a growth chamber. Typical symptoms of Alternaria leaf spot was observed both in in vivo and in vitro inoculated plantlets and detached leaves respectively. Chlorosis on the hypocotyls and leaves were observed. A. alternata was consistently reisolated from symptomatic leaf tissues on PDA. Thus, an efficient and reliable screening method wherein the effect of the selection agent (pathogen culture, culture filtrate/phytotoxin) was demonstrated providing sound pharmacological rational in terms of micro propagation and development of Alternaria resistant L. sativum, an important medicinal herb.